Species variations in the gut microbiota of captive snub-nosed monkeys - Xi, Li; Han, Jincheng; Wen, Xiaohui; Zhao, Longfei; Qin, Xinxi; Luo, Shengjun; Lv, Dianhong; Song, Shuai (Frontiers in Endocrinology, 2023)
Snub-nosed monkeys are species in danger of extinction due to habitat fragmentation and human activities. Captivity has been suggested as an Auxiliary Conservation Area (ASA) strategy. However, little is known about the adaptation of different species of snub-nosed monkeys to captive environments. This study compared the gut microbiota between Rhinopithecus bieti, R. brelichi, and R. roxellana under identical captive conditions to provide insights for improving captive conservation strategies. The results showed that these three Rhinopithecus species shared 80.94% of their Operational Taxonomic Unit (OTU), indicating high similarity in gut microbiota composition. The predominant phyla were Firmicutes and Bacteroidetes for all three Rhinopithecus species, but differences were observed in diversity, characteristic bacterial communities, and predicted function. Significant enrichment of cellulolytic families, including Ruminococcaceae, Clostridiales vadinBB60 group, Christensenellaceae, and Erysipelotrichaceae, and pathways involved in propionate and butyrate metabolism in the gut of R. bieti suggested that it may have a superior dietary fiber utilization capacity. In contrast, Bacteroidetes, Ruminoccaceae, and Trichospiraceae were more abundant in R. brelichi and R. roxellana, and were associated with saccharide and glycan metabolic pathways. Moreover, R. brelichi and R. roxellana also had higher similarity in microbiota composition and predicted function. In conclusion, the results demonstrate that host species are associated with the composition and function of the gut microbiota in snub-nosed monkeys. Thus, host species should be considered when formulating nutritional strategies and disease surveillance in captive snub-nosed monkeys.